2018
DOI: 10.14704/nq.2018.16.4.1209
|View full text |Cite
|
Sign up to set email alerts
|

Reliability Analysis of Driving Behaviour in Road Traffic System Considering Synchronization of Neural Activity

Abstract: This paper aims to disclose the reliability of driving behaviour in road traffic system. For this purpose, the drivers' electroencephalography (EEG) signals were collected with Emotiv, a portable device, and used for an experiment in actual driving environment. Through the analysis on the synchronization of 14-channel EGG signals, the author identified a proper threshold, and determined whether the brain network nodes are connected or not. On this basis, a brain network model was created for the drivers. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Moreover, we found that significantly altered FCs exhibited a long-range frontal-related pattern, leading to increased global and local properties of brain network [38]. These results are consistent with previous findings of other researchers in the study of fatigue-related alterations in brain network [52], [53].…”
Section: Evolution Process In the Fsr Groupsupporting
confidence: 92%
“…Moreover, we found that significantly altered FCs exhibited a long-range frontal-related pattern, leading to increased global and local properties of brain network [38]. These results are consistent with previous findings of other researchers in the study of fatigue-related alterations in brain network [52], [53].…”
Section: Evolution Process In the Fsr Groupsupporting
confidence: 92%
“…Previous studies have shown that EEG equipment with fewer electrodes (Emotiv) can effectively monitor people’s driving fatigue [24,25,26,27]. The Emotiv EEG acquisition equipment has 14 electrodes (14 channels = AF3, AF4, F3, F4, FC5, FC6, F7, F8, T7, T8, P7, P8, O1, and O2), which is consistent with the 14 electrodes (14 channels = F3, F4, F7, F8, FT7, FT8, C3, C4, TP7, TP8, P3, P4, O1, and O2) on the Neuroscan device selected in this paper.…”
Section: Methodsmentioning
confidence: 99%
“…ensemble) entropy measures (Kar et Subjective measures of self-reported sleepiness, predominantly Karolinska Sleepiness Scale (KSS) (Åkerstedt and Gillberg 1990), have been the most common measure as the ground truth of the classification methods in these studies (Kar et al 2010), although this measure has often been supplemented by other physiological or behavioural indicators as well (Zhao et al 2011, Morales et al 2017. While the predominant method of experimentation in this category of studies has been simulated driving, a limited number of studies have tested ADSD system applications in real-world field driving settings (Perrier et al 2016, He et al 2018). In the majority of studies in this category, sleepiness is involved by sustained and monotonous driving in the simulated (or field) setting.…”
Section: Brain Activity Of Fatigued/drowsy Driversmentioning
confidence: 99%